Calcium in the prevention of postmenopausal osteoporosis: EMAS clinical guide. (January 2018) - Cano, Antonio; Chedraui, Peter; Goulis, Dimitrios G.; Lopes, Patrice; Mishra, Gita; Mueck, Alfred; Senturk, Levent M.; Simoncini, Tommaso; Stevenson, John C.; Stute, Petra; Tuomikoski, Pauliina; Rees, Margaret; et al.
Highlights: Insufficient calcium intake increases fracture risk. Guidelines recommend that calcium intake should be between 700 and 1200 mg per day after menopause. Diet should be the preferred source of calcium. Calcium intake above the recommended amount does not reduce fracture risk. Whether excess calcium intake is harmful is debatable. Abstract: Introduction: Postmenopausal osteoporosis is a highly prevalent disease. Prevention through lifestyle measures includes an adequate calcium intake. Despite the guidance provided by scientific societies and governmental bodies worldwide, many issues remain unresolved. Aims: To provide evidence regarding the impact of calcium intake on the prevention of postmenopausal osteoporosis and critically appraise current guidelines. Materials and methods: Literature review and consensus of expert opinion. Results and conclusion: The recommended daily intake of calcium varies between 700 and 1200 mg of elemental calcium, depending on the endorsing source. Although calcium can be derived either from the diet or supplements, the former source is preferred. Intake below the recommended amount may increase fragility fracture risk; however, there is no consistent evidence that calcium supplementation at, or above, recommended levels reduces risk. The addition of vitamin D may minimally reduce fractures, mainly among institutionalised people. Excessive intake of calcium, defined as higher than 2000 mg/day, can be potentially harmful. Some studies demonstrated harm even at lower dosages. An increased risk for cardiovascular events, urolithiasis and even fractures has been found in association with excessive calcium intake, but this issue remains unresolved. In conclusion, an adequate intake of calcium is recommended for general bone health. Excessive calcium intake seems of no benefit, and could possibly be harmful.